2021
DOI: 10.1021/acsomega.1c00756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Shale Oil Reservoir and the Oil Enrichment Model for the First Member of the Lucaogou Formation, Western Jimusaer Depression, Junggar Basin, NW China

Abstract: The Lucaogou Formation (Fm) in the Jimusaer depression is the first large-scale development of a terrigenous clastic sedimentary shale oil reservoir in China. Nearly one billion tons of shale oil resources have been discovered. However, the current exploration and development is concentrated in the eastern part of the sag. The limited geological understanding in the western area has restricted the prediction and development of “sweet spots” for shale oil. To help rectify this, we have studied the petrology, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Most of the soil pore size of Jiangsu paddy soil, Jiangxi red earth, Hunan red earth, and Guizhou yellow soil was lower than 7.5 μm, and the pore volumes were 0.0243, 0.052, 0.0462, and 0.0317 cm 3 /g, respectively. This phenomenon was due to the fine-grained soils with high content that could easily enter the interior of the mesopores, which reduced the connectivity of soil pores and formed fine pores [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the soil pore size of Jiangsu paddy soil, Jiangxi red earth, Hunan red earth, and Guizhou yellow soil was lower than 7.5 μm, and the pore volumes were 0.0243, 0.052, 0.0462, and 0.0317 cm 3 /g, respectively. This phenomenon was due to the fine-grained soils with high content that could easily enter the interior of the mesopores, which reduced the connectivity of soil pores and formed fine pores [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen G. H. et al (2018) reported that 80% of shale oil is distributed in macropores. In fact, with increasing pore size, pore volume and porosity, the oil content in shales usually increases (Wang et al, 2019b;Song et al, 2020;Wang B. Y. et al, 2021). Because the density of the generated oil and gas is lighter than that of kerogen, the volume expansion and the overpressure phenomenon occurs in shales, resulting in the generation of oil expulsion fractures (Sun L. D. et al, 2021).…”
Section: Control Of Toc Content Oil Storage Space and Mineral Composition On Oil Retentionmentioning
confidence: 99%
“…In recent years, an increasing number of studies on shales has been performed on their evolution of hydrocarbon generation, retention and expulsion (Shao et al, 2020;Song et al, 2021a;Sun J. et al, 2021;Hou et al, 2021b;Song et al, 2021b;Stockhausen et al, 2021), oil retention mechanism (Ritter, 2003;Tian et al, 2014;Li et al, 2016;Qiu et al, 2016;Han et al, 2017;Tian et al, 2017;Hou et al, 2020), influencing factors of shale oil enrichment (Han et al, 2015;Zou et al, 2019a;Sun et al, 2019;Chen et al, 2020;Milliken et al, 2021) and geological evaluation (Lu et al, 2012;Kumar et al, 2017;Hu et al, 2018;Qian et al, 2018;Wang et al, 2019b;Li J. B. et al, 2020b;Wang B. Y. et al, 2021). Literatures on shale oil are increasing year by year, shale oil has become a hot topic, and Chinese scholars have carried out much shale oil research work and achieved outstanding contributions (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon is known as the “oil crossover effect”, and the higher the OSI is, the more content of movable oil will be. However, when the pyrolysis S 1 and TOC values are low, the OSI may also have a high value . Therefore, it is necessary to combine the hydrogen index (HI), production index (PI), and other parameters to determine the optimal oil effective flow point. , Second, recent studies have shown that shale oil cannot be released completely before 300 °C. , Therefore, S 1 is not entirely free oil, and S 2 does not completely represent the kerogen hydrocarbon generation potential .…”
Section: Introductionmentioning
confidence: 99%